Inocybe vaurasii (Agaricales, Inocybaceae), a new species of the I. xanthomelas group and similar European species with asteriform spores - Esteve-Raventós, Fernando; Pancorbo, Fermín; Larsson, Ellen; Turégano, Yolanda; Moreno, Gabriel; Altés, Alberto (Phytotaxa, 2022)
Inocybe vaurasii is described as a new species belonging to Section Marginatae group Xanthomelas. A comparative morphological and molecular study has been carried out with other species showing basidiospores with stellate appearance and similar sizes: I. xanthomelas, I. humilis and I. subrimosa. An ITS bar code was obtained from type materials of all three of these species. The molecular analysis reveals that, despite the similarity in spore-shape, none of the species were closely related, but form distinct clades that are spread out within the Xanthomelas group. SEM photographs of the spores are provided for each of the species studied. A lectotype for I. subrimosa is designated and validated and the lectotype previously designated for I. xanthomelas is here validated.